Sargassum-based potential biosorbent to tackle pollution in aqueous ecosystems – An overview - Sara Saldarriaga-Hernandez; Erik Francisco Nájera-Martínez; María Adriana Martínez-Prado; Elda M. Melchor-Martínez (Case Studies in Chemical and Environmental Engineering, 2020)
The uncontrolled release of toxic pollutants related to anthropogenic processes has threatened biodiversity and the ecological integrity of aqueous ecosystems during years. The bioaccumulation and biomagnification of toxic pollutants at different trophic levels have raised concern. Several bioremediation approaches have been tested for efficient mitigation and removal of toxic compounds such as metal ions from aquatic environments. Biosorption by biodegradable and renewable sources such as micro and macroalgae biomass has an increasing scope. However, the biosorption mechanisms of Sargassum spp. have not been completely elucidated, and there are still some drawbacks to overcome. Sargassum spp. biomass has been recognized to be a natural, renewable, and cost-effective material to arrest pollutants from aqueous systems. This mini-review is a compendium that spotlights the potentialities of Sargassum-based biosorbents as an alternative for the removal of toxic contaminants from aquatic environments. Main biosorption mechanisms, key factors influencing biosorption, and the challenges regarding its implementation are highlighted with suitable examples.